Study of the things that affect the income of coconut farmers - Apriliana, Natasya; Elia, Andrie; Zakiah, Wiwin (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2023)
The objective of this research is as follows: The objective is to identify and examine the variables that impact the earnings of coconut growers in the Mentaya Hilir Selatan District. The research findings indicate that the variables of land area (X1), productivity (X2), and pricing (X3) have a simultaneous impact on the income variable (Y). This implies that the independent variables have a concurrent and tangible impact on income or variable (Y) as a whole. The recommendations that can be derived from the findings of this research to enhance outcomes are: The aim is for the findings of this study to serve as a reference and assessment for enhancing coconut business management. Particularly while initiating a coconut cultivation enterprise in Sebamban Village, Mentaya Hilir Selatan District